Pengaruh Pelatihan, Kompetensi Dan Motivasi Terhadap Kinerja Pegawai Primkop Kartika Ardagusema Pussenarmed Cimahi - Maulana, Arman; Nurwati, Ucu (Koaliansi : Cooperative Journal, 2021)
The source of research data is Kartika Cooperative Ardagusema Pussenarmed Primary Staff of Cimahi City Cimahi. The number of data sources is 192 people. With research data on training, competence, motivation on performance. Based on the conclusions of this study, the implications of the training representations included in the sufficient categories. The implication is in management training and improvement in management training. The activity, discussed the stages of formation, transition, core activities, and termination. This causes an increase in the level of participation, unable to control themselves, adjust to the environment, and develop optimal potential so that it does not produce independence in his life at work. Based on the findings in the study, delivered; 1) If the higher the competency, the more energy, facilities, infrastructure, use, methods, media, and financing, the client's tendency to develop its potential optimally the faster it gets independence at work; 2) If the more qualified the training, the more personnel, facilities, needs, methods, and learning media, then the tendency to increase participation is more active in participating in competency improvement activities, and 3) If more qualified, supported by the support provided, then the training is sufficient, and competency is getting better too.